Correlates of migration networks among recent out-migrants from Ankasha District of the Amhara National Regional State, Ethiopia - Arega, Chalachew; Gurmu, Eshetu; Tolossa, Degefa (Ethiopian Journal of Social Sciences, 2024)
Ethiopia has been one of the hot spots for internal migration during the last three decades, where massive rural-to-urban migration took place all over the country due to socio-demographic and political changes. This study primarily aimed at examining the migration network among migrant-sending households in the Ankasha District of the Amhara National Regional State, Ethiopia. The cross-sectional study was employed based on migrant-sending and non-sending households, who were randomly selected from six kebeles of Ankasha District. The study employed Ordinary Least Square Regression analysis techniques to assess the possible impacts of the outmigration of at least one household member on four outcome variables (asset-based wealth, expenditure on agriculture input, expenditure on health, and education of left behind household members). The result showed that the likelihood of having a higher network decreases by about 78% (OR= .221; CI: 0.082-0.595) for those household sizes of <4 members at the place of origin. On the contrary, migrants originating from a household size of 8+ had a 2.47 times higher likelihood of having better networks with sending communities compared to the reference category. Migration network was 3.73 times higher (CI: 1.79- 7.736) among migrants having formal education compared to those having no formal education. The likelihood of migrants having higher networks with sending communities decreased by about 59.6% for those who stayed at the place of destination for <6 months compared to those who stayed for more than 3 years. The findings imply the need to establish ways to monitor the dynamics of impacts of migration on both sending households and migrants themselves. There has been limited research on migration networking in Ethiopia in general and the study area in particular. This calls for an in-depth analysis and the need to examine migration in a wider context of the development agenda based on more reliable longitudinal data.